The Condition of and Structural Changes in the Energy Sector of Ukraine - Miliutin Hlib V. (Problemi Ekonomiki, 2017)
The article is dedicated to the analysis of the condition of Ukraine’s energy sector and its structural changes in the period 2000-2016. The dynamics of electric power production in Ukraine and the world, as well as the capacity utilization factor are studied. There analyzed the structure of capacities and electric power production in Ukraine by types of generation: those of thermal power plants, nuclear power plants, combined heat and power plants, hydroelectric power plants, and renewable energy sources. The lifetime of the existing capacities is studied. Structural changes in the capacities and electric power production in Ukraine are investigated. It is proven that a tendency to reduce the electric power production in Ukraine, with a simultaneous increase in the world production, was observed; and that most of production capacities in the nuclear, thermal and hydropower sector have expired their design lifetime and require replacement or modernization. It is determined that the structural changes in capacities and electric power production in Ukraine in the period 2000-2016 were very low with the largest structural change in capacities and electric power production in the period under review taking place in the production of electricity from renewable energy sources, and a significant negative structural change – in the production of electricity in thermal power plants.